DETERMINANTS OF RESIDENTIAL LOCATION CHOICE IN ISTANBUL: A LONGITUDINAL STUDY - Salihoglu, Tayfun; Turkoglu, Handan (Open House Int, 2019)
Residential mobility is a dynamic urban process resulting from the ever changing internal and external factors of households' residential preferences. Factors effecting these preferences are related to households'perception of spatial issues such as the characteristics of a house, accessibility to urban functions and transportation, land values and house prices, neighborhood characteristics, residential satisfaction, and attachment. The effects of these issues vary through the life cycle as well as social, economic, and employment status of a household. As a result of the legal arrangements and state incentives that have helped to develop the construction industry, current housing patterns have shifted in Istanbul since the 2000s'. This study aims to investigate the changing trends in the factors that affected the residential location preferences of Istanbulites from 2006 to 2014. Data was collected through a stratified sampling method from two different surveys in 2006 and 2014 . The paper explains the change in the destination choice of residents in the city at the district level and furthermore, changes in the households' intention to move to one of the three different housing patterns which are common in the city.
Keywords: Residential Location; Residential Preferences; Residential Mobility; Residential History; Housing Patterns